Video Utilization in Improving Student Achievement in Early Childhood Education - Baso Intang Sappaile; Jenal Abidin; Siti Aisyah (Yayasan Adra Karima Hubbi, 2024)
Background. Video media in learning can have an impact in the field of education, especially in early childhood to help children's growth and development, video as a three-dimensional system that has an important role. Purpose. The study aims to determine the utilization of video in improving early childhood achievement. Method. The method used is quantitative method, the research format is Survey Study. The data collection technique used is communication technique. Data tools are collected in the form of questionnaires and documents. In-depth data analysis This research uses percentage analysis. The sample in this study was 50 people. Results. The results of this study indicate that learning videos can improve student achievement in learning in early childhood education. Conclusion. The conclusion of this study is that with learning video media, children become more confident and make it easier for early childhood to absorb material delivered by educators, and can assess children's activeness directly.